Exploring Stress Factors and Resilience Experienced by Sumbanese EFL Teachers: A Critical Incident Technique Approach - Heda, Ayuni Kabobu; Mbato, Consilianus Laos (Language Circle: Journal of Language and Literature, 2022)
Many researches indicated the EFL teachers’ factors of stress and the key to stay resilient. Stress vestiges the common issue in the teaching field. The attitude of resilient was the main point to assist the teachers in discovering the happiness and keeping them settle sustained at their profession as an educator. Stress factors experienced by educator are enhanced in this pandemic situation. This research was endeavoured to investigate the stress factors and resilient attitudes experienced by teachers in Sumba Island which was one of the remote area in Indonesia. The data was taken by accomplishing an in-depth interview with four teachers who were teaching in Sumba Island. The result revealed that there were some factors might lead the students stress in teaching in rural area, they were; students, lack of resources and facilities, technology awareness, different opinion with colleagues, and the sense of insecurity in teaching in isolated area. The strategic attitude of resilient developed by the teacher to cope with all of those stress were; optimistic attitude, taking a personal approach, self-introspection, keep in mind about job-consequences, and sharing about the problem with others. This research proposed to give further insight into the existences of teachers working in a rural area like Sumba Island, in specific how they ascertain their profession upon all of the stress factors they encountered. The result and conaclusion were presented in descriptive method.